Association between probiotic, prebiotic, and yogurt consumption and chronic kidney disease: The NHANES 2010–2020 - Liu, Xiaoxian; Gao, Wenyan; Yang, Jie; Mao, Genxiang; Lu, Hong; Xing, Wenmin (Frontiers in Nutrition, 2022)
Background: Previous studies suggested that gut dysbacteriosis may promote the occurrence of chronic kidney disease (CKD), and probiotic, prebiotic, or yogurt supplements may alleviate CKD progression. This study aims to examine the association between probiotic, prebiotic, or yogurt supplements and the risk of CKD using the data from NHANES. Methods: This study was designed to prospectively search data from the National Health and Nutrition Examination Survey (NHANES) (2011-2020). We examined dietary supplements and prescription medication labels to identify probiotic, or prebiotic product, and yogurt consumption during the dietary interview. The diagnosis of CKD was determined by the value of glomerular filtration rate (eGFR) and albumin creatinine ratio (ACR). Results: The study enrolled a total of 6522 individuals. The prevalence of CKD was lower in the probiotic, prebiotic, or yogurt consumption group (age-adjusted odds ratio (OR): 0.77, 95% CI: 0.62-0.95, P=0.02; multivariable-adjusted OR: 0.86, 95% CI 0.69-1.07, P=0.05). Furthermore, 32% reduced risk was observed in the older group aged 55 years or older, and 32% reduced risk was also observed in the female population. Probiotic, or prebiotic, or yogurt supplements was associated a 12% reduction in moderate risk of CKD and an 11% reduction in very high risk of CKD. Conclusion: Our results suggest that probiotic, prebiotic, or yogurt supplements may contribute to the prevention of CKD and relieve its progression risk, especially in the female population and older population who were aged 55 years or older.